2015
DOI: 10.1007/s00253-015-7201-1
|View full text |Cite
|
Sign up to set email alerts
|

EGFP reporter protein: its immunogenicity in Leishmania-infected BALB/c mice

Abstract: Optical reporter genes such as green fluorescent protein (GFP) and luciferase are efficiently and widely used in monitoring and studying the protective/therapeutic potential of candidate agents in leishmaniasis. But several observations and controversial reports have generated a main concern, whether enhanced GFP (EGFP) affects immune response. To address this issue, we studied the immunogenicity of EGFP in vivo by two lines of stably transfected parasites (Leishmania major (EGFP) or L. major (EGFP-LUC)) in BA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 41 publications
0
10
1
Order By: Relevance
“…Although there was no significant difference between G1 (L. lactis-PpSP15-EGFP cwa ) and G2 (L. lactis-EGFP cwa ) in both ST and LT experiments, the mean±SD in G1 was lower than in G2. However, immunogenicity of EGFP is a controversial subject [50][51][52]. However, foodpad swelling in mice by itself is not a valid indicator of the potential efficacy of vaccination or the infectivity rate [53].…”
Section: Discussionmentioning
confidence: 99%
“…Although there was no significant difference between G1 (L. lactis-PpSP15-EGFP cwa ) and G2 (L. lactis-EGFP cwa ) in both ST and LT experiments, the mean±SD in G1 was lower than in G2. However, immunogenicity of EGFP is a controversial subject [50][51][52]. However, foodpad swelling in mice by itself is not a valid indicator of the potential efficacy of vaccination or the infectivity rate [53].…”
Section: Discussionmentioning
confidence: 99%
“…The regional draining popliteal lymph nodes (dLNs) were dissected from each individual mice (n = 5) and homogenized for parasite burden calculation, as previously described. 15 Briefly, the homogenates at each dLNs were serially diluted 5-fold (ranging from ~1 1 to ~10 15 ) and dispensed in 96-well micro-titration flat-bottom plates in duplicate. Plates were examined by inverted microscope, and the last dilution with at least one viable promastigote was selected as the end titre.…”
Section: Determination Of Parasite Burden By Limiting Dilution and mentioning
confidence: 99%
“…At different intervals (1 and 3 mo after the Ltrop inoculation, and 1 and 2 mo after Lmj inoculation), popliteal dLNs of mice (5 mice per group) were extracted and homogenized to be used for parasite burden quantification. The homogenized dLNs were serially diluted 5-fold (ranging from ~1 1 to ~1015 ) and dispensed into 96-well plates in duplicate (A and C). All wells were examined by inverted microscope, and the last dilution with viable promastigote was selected as the final titre for calculation of parasite burden.…”
mentioning
confidence: 99%
“…Other reports have identified immunodominant epitopes of EGFP and DsRed proteins, which induce a CTL response in BALB/c and C57BL/6 mice . A further study by Seif et al . showed that despite a lack of evidence of EGFP immunogenicity in Leishmania major infected BALB/c mice, they found enhanced lesion sizes and increased parasite burdens .…”
Section: Introductionmentioning
confidence: 97%
“…A further study by Seif et al . showed that despite a lack of evidence of EGFP immunogenicity in Leishmania major infected BALB/c mice, they found enhanced lesion sizes and increased parasite burdens . The aforementioned experimental models using reporter proteins call for an analysis of the possible immunogenicity of fluorescent proteins when used in transgenic parasite models for biological studies.…”
Section: Introductionmentioning
confidence: 99%